2003
DOI: 10.1038/sj.ijir.3900968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction and its correlates: a population-based study in Morocco

Abstract: To obtain data on the prevalence of erectile dysfunction (ED) and its correlates, along with helpseeking behaviour, 655 randomly selected men at least 25 y old, residing in Casablanca, Morocco, were recruited. They responded to a questionnaire administered by five trained sociologist interviewers. Information on demographics, concomitant diseases, drugs, and sexual activity was collected. ED was prevalent in 54%, increased noticeably with age, and was highly prevalent between both the illiterate and those empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
39
3
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 12 publications
11
39
3
6
Order By: Relevance
“…33 It has also been shown that coffee intake does not have an effect on ED, 11,34 and it is also supported by this study.…”
Section: Effect Of Life-style Factors On Ed R Shiri Et Alsupporting
confidence: 67%
“…33 It has also been shown that coffee intake does not have an effect on ED, 11,34 and it is also supported by this study.…”
Section: Effect Of Life-style Factors On Ed R Shiri Et Alsupporting
confidence: 67%
“…The results of this epidemiologic analysis, like that of Berrada et al, 4 indicated that the prevalence of ED and other diseases associated with this condition in sub-Saharan Africa, the Middle East, and south Asia is similar to that in the United States and Western Europe. Surveys of men between 35 and 70 y of age seeking primary medical care indicated that the age-adjusted prevalences of ED were 57.4% in Nigeria, 63.6% in Egypt, and 80.8% in Pakistan.…”
Section: Introductionsupporting
confidence: 49%
“…Similar estimates have been reported in studies conducted in Australia, 18 Brazil, 19 Egypt, 30 France, 31 Germany, 22 Netherlands, 32 Spain, 2 and UK. 26 Considerably higher estimates have been reported in studies from Australia, 17 Belgium, 33 Brazil, 20,21 Finland, 34,35 Italy, 20 Japan, 20 Mexico, 28 Morocco, 27 Thailand, 24 Turkey, 36 USA, 6,8,37 and lower estimates in Denmark 38 and Sweden. 5 Thus, our prevalence estimates are often lower and thus more conservative than in many of the other studies.…”
Section: Commentsmentioning
confidence: 93%
“…Although there are a number of methodological differences between the various studies, such as the age range of the men included in the analyses and the definition of dysfunction that was applied, we have attempted to compare the estimates of prevalence of sexual dysfunction in GSSAB surveys with those reported in the literature (most published studies report only erectile dysfunction), including the US, 3,6,8,9 Australia, 17,18 Brazil, [19][20][21] Germany, 22 Italy, 20,23 Thailand, 24 Spain, 25 the UK, 4,26 Malaysia, 20 Japan, 20 Morocco, 27 Mexico, 28 Korea, 29 and other countries and subpopulations. 2,[30][31][32][33][34][35][36][37][38][39] The ageadjusted estimates of prevalence of erectile dysfunction in GSSAB ranged from 13 to 28% across the seven regions.…”
Section: Commentsmentioning
confidence: 99%